Risk analysis of road traffic accidents in Ukraine - Lyashuk, Oleg; Mironov, Dmytro; Martyniuk, Volodymyr; Aulin, Viktor; Tson, Oleg; Maruschak, Pavlo (Transport, 2024)
This article presents a comprehensive investigation into the causes of road transport accidents in Ukraine, focusing on the application of risk analysis to minimize economic and human losses. The study begins with a detailed examination of the current road safety scenario in Ukraine, highlighting the alarming statistics of road accidents and their consequences. The central aim is to develop effective strategies for controlling and managing the causes of road accidents. The research identifies the primary factors contributing to road accidents, such as exceeding safe speed limits, driving under the influence of alcohol, etc. A risk management system is proposed, encompassing the creation of a structured risk management framework, development of methodologies, and implementation of information and analytical systems. The article emphasizes the importance of continuous risk monitoring and assessment, including risk identification, analysis, and management. Statistical observations and analysis play a crucial role in diagnosing risks, which are then used to devise risk minimization measures and improve road safety. The study concludes with recommendations for risk-based decision-making and the implementation of targeted interventions to reduce road accidents and associated risks in Ukraine. First published online 11 February 2025